Effect of active and passive recovery on blood pressure and heart rate in male athletes - Sahraei, F.; Khoshnam, E.; Nikseresht, E. (European Journal of Experimental Biology, 2013)
Recovery is one of the most important stages of training. Lack of recovery makes the athletes not to benefit enough from exercises. The purpose of the present study was to investigate the effects of active and passive recovery on systolic and diastolic blood pressures, and heart rate in male athletes. 20 young volunteer athletes were assigned in active recovery (n=10) and passive recovery (n=10) groups. Subjects performed cooper test. Subjects' blood pressure and heart rate were measured immediately after the test, and 20 minutes after the test. Data analysis was performed using dependent and independent T- test. Findings showed that there were significant differences in heart rate and systolic blood pressure values between active and passive recovery groups between the two stages, immediately after and 20 minutes after the test (p=0.0001). There were no significant differences in diastolic blood pressure values at the two stages. Also no significant differences in blood pressure and heart rate between groups were observed. Results showed that there were no significant differences between passive and active recovery on systolic and diastolic blood pressures, and heart rate in athletes.